إدمان الانترنت عند طلاب بعض الجامعات بولاية الخرطوم - رابح، أنس الطيب الحسين (مركز البصيرة للبحوث والاستشارات والخدمات التعلمية, 2011)
تناولت هذه الدراسة موضوع "إدمان طلاب بعض الجامعات بولاية الخرطوم للإنترنت " ، وتهدف إلى التعرف على إدمان الإنترنت ومن ثم دلالات الفروق في ظل بعض المتغيرات الأخرى. تم استخدام المنهج الوصفي نسبة لأهميته في مثل هذه البحوث، وبلغ حجم عينة الدراسة (150) طالبا وطالبة اختيروا بأسلوب العينة العشوائية المتساوية، كانت أداة الدراسة مقياس إدمان الإنترنت من إعداد الباحثة أماني ضرار (2011). وقد حقق الخصائص السيكومترية في جانب الصدق (0.87) وفي جانب الثبات (0.76). تم استخدام برنامج " الحزم الإحصائية للعلوم الاجتماعية " لغرض المعالجة الإحصائية.\ انتهت الدراسة إلى نتائج تمثلت في أن طلاب بعض الجامعات بولاية الخرطوم يتسمون بخاصية إدمان الإنترنت ، فضلاً عن وجود فروق ذات دلالة إحصائية في جانب متغير النوع، وعدم وجودها في متغير العمر ختمت الدراسة بمقترحات وتوصيات . This study 4 which comes under the title “Internet Addiction by Some Students in Khartoum State”. Aims to identify the phenomenon of internet addiction, and the indications of differences under some variables. Due to its significance in such studies, the descriptive method was applied here, and the sample of the study comprised (150) subjects chosen by the equalizing random sampling method. The tool of the study was “ the internet addiction scale” prepared by the researcher AmaniDirar (2011).\ The psychometric characteristics scored (0.87) in terms of validity and (0.76) in terms of reliability. The researcher used the SPSS programm for the purpose of statistic processing.\ The results of the study indicated that students at some universities in Khartoum State have some degree of internet addiction. Furthermore, there were statistically indicative differences with regard to the “sex” variable, but there were no such differences with regard to the “age” variable. At the end of the study, the researcher proposed some suggestions and recommendations for related future studies.
Keywords: تكنولوجيا الاتصالات -- الخرطوم -- إدمان الإنترنت -- الطلاب -- الجامعات والكليات -- الانترنت -- ثورة المعلومات -- أوقات الفراغ